HUBUNGAN ANTARA BEBAN KERJA DENGAN GANGGUAN POLA TIDUR PADA PERAWAT DI INSTALASI GAWAT DARURAT NON TRAUMA RSUP PROF DR. R. D. KANDOU MANADO - Tareluan, Devina Gian; Bawotong, Jeavery; Hamel, Rivelino (JURNAL KEPERAWATAN, 2016)
Abstract : Sleeping is the basic need for humanbeing without the enough amount of both rest and sleeping, the ability in contrentration, making decision, and participating in daily activites will decrease. The aim of this research: is to find out the relation of work responsibility with the discruption of sleeping habit to the nurses in Non Trauma Emergency Care Unit of Prof. Dr. R. D. Kandou General Hospital Manado. The Method of the research: was in characteristic of analytical observational with cross sectional approach. The sample that taken was total sampling with 32 respondents. The instrument that used in this research was questioner. The result of this research was using chi square statistically test analysis with its meaning level was Î± = 0.05 or 95%. The result of statistic test be found the value p = 0.006 < Î± = 0.05. Conclusion: there is relationship between nurses work responsibility with the discruption of the sleeping habit to the nurse in Non Trauma Emergency Care Unit of Prof. Dr. R. D. Kandou General Hospital Manado. Suggestions : The nurses suggested to arrange their time very well such as how to use their time after work, and get rest before continue their next activities and also keep their own stamina before doing their official duty so that they will be able to do their job effectively. Keywords : Workload, Sleep Patterns, Nurses Abstrak : Tidur merupakan kebutuhan dasar manusia, tanpa jumlah istirahat dan tidur yang cukup, kemampuan untuk berkonsentrasi, membuat keputusan, dan berpatisipasi dalam aktivitas harian akan menurun. Tujuan Penelitian ini adalah mengetahui hubungan beban kerja perawat dengan gangguan pola tidur pada perawat di Instalasi Gawat Darurat Nontrauma RSUP Prof DR. R.D. Kandou Manado. Metode : Penelitian ini bersifat observasional analitik dengan pendepakatan cross sectional. Sampel yang diambil adalah total sampling yaitu sebanyak 32 responden. Instrumen yang digunakan dalam penelitian ini adalah kuesioner. Hasil Penelitian menggunakan analisis uji statistik Chi Square dengan tingkat kemaknaan Î± = 0,05 atau 95% Hasil Uji statistik didapatkan nilai p = 0,006 < Î± = 0,05. Kesimpulan dari penelitian ini yaitu ada hubungan beban kerja perawat dengan gangguan pola tidur pada perawat di Instalasi Gawat Darurat Nontrauma RSUP Prof DR. R. D. Kandou Manado. Saran Perawat disarankan agar dapat mengatur waktu dengan baik dimana menggunakan waktu setelah kerja dengan beristirahat sebelum melanjutkan aktivitas selanjutnya dan menjaga stamina sebelum melaksanakan dinas agar dapat bekerja secara efektif. Kata Kunci : Beban Kerja, Pola Tidur, Perawat